Exploration Of Managerial Communication Styles And Employees' Perceptions Of Motivation And Performance - Bayu Ade Prabowo; Shella Gherina Saptiany (LITERACY : International Scientific Journals of Social, Education, Humanities, 2024)
Manager's language style plays a crucial role in influencing employee motivation and performance within an organization. This study aims to explore the relationship between manager's language style, motivation, and employee performance using a qualitative descriptive approach. By relying on existing literature and personal observations in the context of management, this study seeks to provide a deeper understanding of how manager's language style can impact employee perceptions of their motivation and performance. Through thematic analysis of relevant literature, several key themes have been identified, including the importance of clear and positive communication, the impact of motivating language on employee engagement, and the role of constructive feedback in enhancing performance. The findings from this study highlight the need for managers to strategically use language that fosters a positive and motivating work environment, which can ultimately lead to increased employee motivation and performance. Practical implications of this research include recommendations for managers to adopt more effective language styles and for organizations to provide appropriate communication training for their leaders. Although this study has limitations due to its reliance on secondary data sources, the resulting findings provide a strong foundation for further research on the role of language style in management.